EVALUATION OF PATIENT SATISFACTION LEVEL TOWARDS SHARIA-BASED PHARMACY SERVICES AT SUNAN KALIJAGA HOSPITAL, DEMAK REGENCY - Febrinasari, Nisa; Baiti, Mustika; Pradipta, Lioni Regina (Gamma Publishing, 2025)
Pharmaceutical services can be interpreted as a service related to pharmaceutical preparations and directly provided by pharmacists or pharmaceutical personnel to patients with the aim of obtaining effective, safe therapy results so that they can improve patient health. This study aims to determine the level of patient satisfaction to know the characteristics of outpatients and polyclinic departments who receive pharmaceutical services based on sharia values ​​at Sunan Kalijaga Hospital, Demak Regency. based on five dimensions of service quality, namely Responsiveness, Reliability, Assurance, Empathy, and Tangible. The results of the study showed that patient satisfaction based on responsiveness was 97% (Very Satisfactory), reliability was 93% (Very Satisfactory), assurance was 96% (Very Satisfactory), empathy was 95% (Very Satisfactory) and Physical evidence was 96% (Very Satisfactory). It can be concluded that the average of the five dimensions has a percentage score above 90%. So it can be stated that the level of respondent satisfaction can be said to be very satisfied with the pharmaceutical services at Sunan Kaijaga Hospital, Demak Regency.